种废弃压敏电阻的资源化处理方法 (2018)
本发明公开了种废弃压敏电阻的资源化处理方法，属于电子废弃物资源化利用技术领域。本发明的技术方案要点为：种废弃压敏电阻的资源化处理方法，包括溶剂混合流去绝缘漆皮、低温液氮冷冻机械碰撞去除镍铁合金丝及焊锡和高温刮擦及往复筛分回收银屑等步骤。本发明实施过程中无焚烧污染物、含酸废水、含重金属离子废水及废渣的排放，而且整个过程无需燃料燃烧供能，更加节能环保，并且该工艺精细化程度、综合产值及投入产出比远远高出传统处理工艺。 The invention discloses a resourceful treatment method for a waste piezoresistor and belongs to the technical field of resource utilization of electronic waste. According to the technical scheme, the resourceful treatment method for the waste piezoresistor comprises the steps of removing insulating paint skin with solvent mixed flow; removing nickel-iron alloy wires and soldering tin through low-temperature liquid nitrogen refrigeration and mechanical collision; and recycling silver scraps through high-temperature scraping and reciprocating sieving. In the resourceful treatment process of the waste piezoresistor, no incineration pollutant or acid-containing waste water or waste water containing heavy metal ions or waste residue is discharged; in addition, fuel combustion for energy supply is not needed in